Microchannel structure of ceramic membranes for oxygen separation - Shao, Xin; Wang, Zhitao; Xu, Shanshan; Xie, K.; Hu, Xun; Dong, Dehua; Parkinson, Gordon; Li, Chun-Zhu (Elsevier Ltd, 2016)
Microchanneled ceramic membranes have demonstrated superior performance in oxygen separation from air over conventional membranes. In this study, the contributions of the microchannel structure to the superior performance were investigated. Compared with supported membranes, the microchanneled membranes provide fast pathways within the channels for gas diffusion as compared to the tortuous interconnection of pore channels in the supported membranes. The walls of the numerous channels provide a large surface for facilitating oxygen dissociation, which was confirmed by varying the channel wall surface using mesh templates with different aperture sizes. In summary, the microchannel structure facilitates gas diffusion and provides a large membrane active surface, resulting in high performance in oxygen separation.